2020
DOI: 10.1007/978-3-030-25726-2
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Potential of Digital Post-Millennials in the Future Workplace

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Older participants were more hesitant to engage with rTMS as compared with younger participants. This aligns with the Generational Cohort Theory, which suggests that certain life stages coincide with generational beliefs and characteristics 49. For example, this model supports the possibility that limited technological exposure, or exposure to times with less pervasive technology, among older generations may account for their sceptical perceptions towards rTMS when compared with younger individuals 50.…”
Section: Discussionsupporting
confidence: 79%
“…Older participants were more hesitant to engage with rTMS as compared with younger participants. This aligns with the Generational Cohort Theory, which suggests that certain life stages coincide with generational beliefs and characteristics 49. For example, this model supports the possibility that limited technological exposure, or exposure to times with less pervasive technology, among older generations may account for their sceptical perceptions towards rTMS when compared with younger individuals 50.…”
Section: Discussionsupporting
confidence: 79%
“…However, the skills needed for employees in the future are not limited to digital skills and the ability to decide to lead a team, to work to support colleagues, to interact and to present and support a topic with arguments. The members of a remote team must show creativity, ability to conceptualize and entrepreneurial spirit (Okros, 2020). All these skills are all the more important for managers, who today are put in a position to motivate the people they lead remotely.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They can be characterized with similar social features, in other words, a group of people united by age and values, surrounded by the same technological environment, accompanied by the same historical events and experience (Zhitomirsky-Geffet & Blau, 2016;Duffet, 2017;Okros, 2020;Maciaszczyk & Kocot, 2021). According to Llopis-Amoros et al ( 2019), generations might be perceived as a group of individuals, where the members are connected by the same way of thinking, they experience the most important events of their personal biography in the same historical and cultural environment, who will attend educational institutions at the same time, will meet their life partner and choose profession during the same time interval.…”
Section: Generationsmentioning
confidence: 99%
“…The arrival of Generation Z meant the end of clearly defined tasks and traditions, which had been accepted automatically until now. Scientific literature or studies refer to Generation Z as the Zeds, Zees, bubblewrap Kids, The New Millennials, Digital Natives, Wired Generation, Screenagers or iGen (Zhitomirsky-Geffet & Blau, 2016;Duffet, 2017;Okros, 2020;Maciaszczyk & Kocot, 2021). World Health Organization has revealed that this generation has passed through more different life phases than the generations before them.…”
Section: Generationsmentioning
confidence: 99%